2018
DOI: 10.17576/ajag-2018-09-08
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Enterprise Resource Planning Systems and Forms of Management Control on Firm’s Competitive Advantage

Abstract: In the brick of digitalization industry revolution era, this study signifies the pertinent role of Enterprise Resource Planning Systems (ERPs) towards assisting the organization towards attaining the firm's mission and goal. This study extends the knowledge by exploring the relationship between ERPs and management control (MC), which in turn enhances firm's competitive advantage. Realizing the limited empirical work on ERPs from management accounting and control perspective, the discussion would be drawn from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…For routinisation the KM activities are: knowledge accumulation, knowledge sharing, knowledge creation and the application of new KM tools. Alomari et al., (2018) consider the ERP system measurements based on the combination of four attributes of the business process that are integration, standardization, routinisation and centralization of the business process. We believed that the hypotheses H5, H5a, H5c and H5d would be validated, but only the hypothesis H5b was validated, showing that routinisation moderates the relations among the internal operations and the performance in the farm.…”
Section: Resultsmentioning
confidence: 99%
“…For routinisation the KM activities are: knowledge accumulation, knowledge sharing, knowledge creation and the application of new KM tools. Alomari et al., (2018) consider the ERP system measurements based on the combination of four attributes of the business process that are integration, standardization, routinisation and centralization of the business process. We believed that the hypotheses H5, H5a, H5c and H5d would be validated, but only the hypothesis H5b was validated, showing that routinisation moderates the relations among the internal operations and the performance in the farm.…”
Section: Resultsmentioning
confidence: 99%
“…Based on a longitudinal case study conducted in the European department of a great United States multinational, Scapens and Jazayeri [13] established four attributes which are deemed necessary in facilitating changes in organization through ERP implementation. Recently, Alomari et al [29] maintained that the single-instance ERP rolling out was not only about the standardization of technology, but also consisted of the integration of data as well as standardization of business process. Consequently, the current study will look into ERP systems using business process attributes following Scapens and Jazayeri [13] and Sanchez and Spraakman [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Investment in ERP systems in companies comes with the expectation of obtaining the aims in increasing some assets and abilities along with technical and managerial competencies in order for the firm to develop opportunities and values for differential long term major benefits [27]. The implementation of ERP system would directly bring operational advantages through innovation capacity building and stimulation involving the technology that subsequently provide the long-term benefits opportunities and lead to the creation of value [27] which in the long run lead to competitive advantage [28,29]. Previous studies put emphasis on the significance of creating integration which leads to improvement of firm's competitive advantage.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Alomari, Amir, Aziz, and Auzar () conducted a research to explore the relationship between ERP systems and management control (MC), represented by technocratic and socio‐ideological, enhancing an organization's competitive advantage. They found that both technocratic and socio‐ideological associated positively with competitive advantage.…”
Section: Literature Reviewmentioning
confidence: 99%